Effects of soil small strain nonlinearity on dynamic impedance of horizontally loaded suction caisson for offshore wind turbines. Issue 165 (February 2023) - Lai, Huaiyuan; Gu, Xiaoqiang; Tu, Wenbo; Lin, Yifeng; Xiao, Jiandong
Abstract: Suction caisson foundation is receiving increasing attention for its strong capacity of resisting horizontal and overturning loads in shallow water (0–30 m). Though extensive studies have been carried out on its performance under static loading, limited understanding has been reached on the dynamic properties of suction caisson foundation, especially regarding the effect of soil small strain nonlinearity. In this study, finite element method (FEM) is used to capture the dynamic impedance degradation of a typical suction caisson foundation in South China Sea. A series of parametric studies were performed to analyze the effects of soil nonlinearity and soil profile on the dynamic impedance of the suction caisson. The results show that the dynamic impedance of the suction caisson is significantly affected by the load magnitude and the degree of soil nonlinearity. It also indicates that the horizontal stiffness of the suction caisson is closely related to the soil modulus in relatively shallow strata above the skirt tip, while the horizontal-rocking stiffness and rocking stiffness are closely related to the soil modulus below the bottom of the suction caisson. Finally, simple functions are proposed to capture the effects of soil nonlinearity and soil stiffness profile on the dynamic impedance of suction caisson. Highlights: Systematical investigation on dynamic impedance considering the soil nonlinearity. Effects of various factors on the dynamic impedance of the suction caisson. Dynamic impedance of the suction caisson embedded in three soil profiles. Simple functions proposed for the effect of soil nonlinearity on dynamic impedance.